Principles of formation of situation models of air traffic control systems - Білецький, А. Я.; Корчунов, Д. О.; Харченко, В. П. (Proceedings of National Aviation University (archive), 2000)
The fundamental principles of formation of multialternative situation models of air circumstances were enunciated. Probability of objects detection is taken as example of influence of the main characteristic of surveillance of air traffic control system